Kontrola zamówień publicznych dotyczących morskich budowli hydrotechnicznych realizowanych w ramach „Programu ochrony brzegów morskich” - Trela, Anna (Studia Prawa Publicznego, 2019)
The article presents an analysis of the thesis on the existence of a system of controlling public procurements concerning services of the construction of sea shore protection structures. It reviews the audit of such public procurement carried out by the various inspection bodies and different methods of control. The first part of the study contains the characteristics of inspection bodies which carried out audits of public procurement contracts and whose subject matter was sea shore protection structures. It is also indicated that although indirectly, tax revenue agencies, administrative courts and the Ombudsman play an important role in the system. For the purposes of moving on to the discussion of particular types of inspections carried out by various public bodies and courts. In the article, certain works consisting in strengthening the sea shore have been assigned to the category of hydrotechnical structures, which allowed to move on to the discussion of particular types of inspections carried out by various public bodies and courts and to cite conclusions formulated on their basis. The concept of “coastal protection of the marine environment,” which underpinned the adoption of the resolution of the Supreme Administrative Court of 11 December 2017, ref. I FPS 2/17 was also analysed in detail. In this resolution the position of the authoress of this article, expressed earlier in the commentary to the judgment of the Supreme Administrative Court of 14 April 2015, ref. I FSK 1493/14 and published in “Studia Prawa Publicznego” 2016, no. 1 was shared. The conclusion of the deliberations is that the system for controlling public procurements of services related to maritime coast protection is not coherent and mutually supportive. The results of the study show that many activities under this system relating to coastal protection were subject to control by many different authorities, leading in consequence to different conclusions.